Reversible hypogonadotropic hypogonadism in men with the fertile eunuch/Pasqualini syndrome: A single-center natural history study - Dwyer, Andrew A.; Stamou, Maria; McDonald, Isabella R.; Anghel, Ella; Cox, Kimberly H.; Salnikov, Kathryn B.; Plummer, Lacey; Seminara, Stephanie B.; Balasubramanian, Ravikumar (Frontiers in Endocrinology, 2022)
Congenital hypogonadotropic hypogonadism (HH) is a heterogeneous genetic disorder characterized by disrupted puberty and infertility. In most cases, HH is abiding yet 10-15% undergo reversal. Men with HH and absent and partial puberty (i.e., testicular volume <4mL and >4ML respectively) have been well-studied, but the rare fertile eunuch (FE) variant remains poorly characterized. This natural history study of 240 men with HH delineates the clinical presentation, neuroendocrine profile, rate of reversal and genetics of the FE variant. We compared three HH groups: FE (n=38), absent puberty (n=139), and partial puberty (n=63). The FE group had no history of micropenis and 2/38 (5%) had cryptorchidism (p<0.0001 vs. other groups). The FE group exhibited higher rates of detectable gonadotropins, higher mean LH/FSH levels, and higher serum inhibin B levels (all p<0.0001). Neuroendocrine profiling showed pulsatile LH secretion in 30/38 (79%) of FE men (p<0.0001) and 16/36 (44%) FE men underwent spontaneous reversal of HH (p<0.001). The FE group was enriched for protein-truncating variants (PTVs) in GNRHR and FGFR1 and 4/30 (13%) exhibited oligogenic PTVs. Findings suggest men with the FE variant exhibit the mildest neuroendocrine defects of HH men and the FE sub-type represents the first identified phenotypic predictor for reversible HH.